VALUE OF PSYCHOLOGICAL CULTURE IN THE FORMATION PROCESS OF THE FUTURE TEACHER'S PERSONALITY - Pukhno, Svetlana (PSYCHOLOGICAL JOURNAL, 2019)
The theoretical concept analysis of “personality psychological culture” and the components meaning of this phenomenon in the students- future teachers teaching process at the higher educational establishments are presented in the article. Psychological culture is a personal dynamic formation and a professional culture component, which ensures individual self-realization as the professional activity subject is determined in the study. The psychological culture components are analyzed: cognitive, reflective-perceptual, communicative, regulatory, value-semantic. It is presented that these components formation of the students’ psychological culture occurs as a result of the future teachers’ personal characteristics transformation in the course of educational activities subject to the innovative educational technologies introduction. In order to determine the psychological culture value in the formational process of the future teacher’s personality, during the 2018-2019 school year, an experimental study was conducted on the Physics and Mathematics Faculty basis of Makarenko Sumy State Pedagogical University, in which undergraduates - future teachers of computer studies, mathematics, physics have participated. All participants have got pedagogical experience: passing a long pedagogical practice, working at children health centers, secondary schools, colleges. These students have studied the disciplines "Psychology", "Pedagogy" during the І-ІІ courses, performed individual educational research tasks and research on topical issues of general, social, age and pedagogical psychology, pedagogy, participated in social trainings, were members of student scientific circles, participated with author's research results at scientific conferences. As a result of the first study stage, the self-esteem features of the professionally important pedagogical qualities of future teachers’ of computer studies, mathematics, and physics were identified. This is a dynamic formation, which is provided due to the person’s assessments of his potential qualities as a future specialist. The formation of psychological culture components is a factor in objective self-esteem of the future teacher’s professionally important qualities: students, who have got psychological knowledge and reflexive thinking system, objectively assess their professional characteristics and realize the need for their development. The study results indicate that undergraduates of Makarenko Sumy State Pedagogical University evaluate their own professionally important qualities as future teachers at a high level, as political convictions, general culture, erudition, professional pedagogical orientation, moral and volitional qualities, didactic and expressive speech abilities, academic and organizational communication skills. Such professionally important pedagogical qualities as perceptual abilities, pedagogical imagination, abilities to distribute attention at the lesson and authoritarian abilities are assessed by undergraduates at an insufficient level, which requires extra-work on their development. As a result of the second study part, the professional orientation features of future teachers of computer studies, mathematics, and physics were determined. It is presented that for the majority of studied young people, a professional type orientation “Teacher-Subject” is characteristic, which indicates the future teachers’ professional competence acceleration, the desire for pedagogical creativity and innovation. This requires the academic, didactic, communicative and prognostic abilities development, which is possible providing innovative educational methods into the educational process of the higher educational establishments. These problems require the modern researchers’ attention in the psychology and pedagogy field of higher education in order to develop effective teaching technologies.